A case of Guillain-Barre syndrome with pregnancy who delivered in ICU: a rare outcome of rare co-occurrence. Issue 11 (7th November 2019) - Jain, Rahul; Rathi, Pankaj Satyanarayan; Telang, Kapil; Zaidi, Alia
Abstract : Guillain-Barre syndrome (GBS) in pregnancy is a rare co-occurrence and it is generally accepted that it carries a high maternal risk. We report a 40-year-old housewife who developed GBS with respiratory failure during the third trimester (31 weeks of gestation). She had preterm vaginal delivery on ventilator support at 34 weeks of gestation in neurology intensive care unit. She managed successfully with ventilatory support, intravenous immunoglobulin and other supportive measures.